2014
DOI: 10.5012/bkcs.2014.35.8.2519
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Electrocatalytic Amplification of Iridium Oxide (IrOx) Single Nanoparticle Collision on Copper Ultramicroelectrodes

Abstract: Recently, the observation of the electrocatalytic behavior of individual nanoparticles (NPs) by electrochemical amplification method has been reported. For example, the Iridium oxide (IrO x ) NP collision on the Pt UME was observed via electrocatalytic water oxidation. However, the bare Pt UME had poor reproducibility for the observation of NP collision signal and required an inconvenient surface pre-treatment for the usage. In this manuscript, we has been investigated other metal electrode such as Cu UME for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…In recent years a number of reviews has been published in the field of nano impact. , Scientists have used several methods to observe the impact of nanoparticles on the electrode surface. These methods include electrocatalytic current amplification (ECA), , potentiometric method, anodic particle coulometry (APC), cathodic particle coulometry (CPC), and blocking method . Beside determining the size distribution of nanoparticles, these methods are able to estimate their surface activity .…”
mentioning
confidence: 99%
“…In recent years a number of reviews has been published in the field of nano impact. , Scientists have used several methods to observe the impact of nanoparticles on the electrode surface. These methods include electrocatalytic current amplification (ECA), , potentiometric method, anodic particle coulometry (APC), cathodic particle coulometry (CPC), and blocking method . Beside determining the size distribution of nanoparticles, these methods are able to estimate their surface activity .…”
mentioning
confidence: 99%
“…The collision mechanism of a single NP collision can be classified as hit-n-run, hit-n-roll, or hit-n-stay, depending on the state of the NP after the collision event [7]. In particular, when Cu was used as a UME to observe the single-NP collision signals of Pt NPs and IrO x NPs, it was observed that the collision frequency was significantly reduced to ~1/3000 for Pt NPs and ~1/4 for IrO x NPs compared to the other electrode materials [38,39]. Therefore, we believe that the reduced frequencies are because of the weak interaction between the NPs and Cu UME, which leads to a hit-n-run mechanism in which the colliding Ag NP does not adhere well to the Cu UME.…”
Section: Resultsmentioning
confidence: 99%